GAMBARAN PERSEPSI ORANG TUA TENTANG VAKSINASI COVID-19 DI SDIT ADZKIA 2 KOTA PADANG - Adella Aprilia; Rendri Bayu Hansah; Nurwiyeni (Yayasan Nusantara Hasana Berdikari, 2023)
Background: Children of all ages runs the risks of being exposed to an infectious agent sars-cov-2 and the manifestation of illness.Vaccination covid-19 to children aged 6 11 years has begun since december 2021 as one of the main prevent transmission of covid-19.The number of people who had dissented old their children in order to vaccinated with reason the absence of government accountability when vaccination had an impact on the health of children, worry the purpose of vaccination is not for health and fear that the vaccine is not yet tested.Aims: This study aims to find out the Picture of Parents' Perception About COVID-19 Vaccination at SDIT Adzkia 2 Padang City. Methods: This type of research is descriptive categorical with a cross-sectional approach that uses primary data derived from questionnaires given to respondents according to the criteria for describing parents' perceptions of COVID-19 vaccination at SDIT Adzkia 2 Padang city. The sampling technique of this study uses consecutive sampling techniques. The sample obtained was 100 people. Results: The research results show sexes respondents most were women made up 70 %, the age of respondents most were 40-49 of these families are 51 %, the level of education last respondents most were scholar namely 94 %, most were the kind of work the 2009 an army / police / bumn / bumd namely 42 %.And, perceptions on urgency vaccination covid-19 on child most were perception enough that is 50 percent, perception about the side effects of vaccination covid-19 on child most were perception enough namely 58 % and perceptions about the safety of the vaccination covid-19 on child most were enough that is 54 % perception. Conclusion : The most of parent’s perceptions regarding the urgency, side effects and safety of COVID-19 vaccination in children are in the sufficient category in SDIT Adkia 2 Padang city.